APLIKASI PENGOLAHAN DATA NILAI SISWA DI SMA NEGERI 1 AMANUBAN SELATAN MENGGUNAKAN VISUAL BASIC 6.0 - Amalo, Verawaty Yusmarni; Rachmawati, Rr.Yuliana; Andayati, Dina (Jurnal Script, 2014)
ABSTRACTSMAN 1 South Amanuban has used manual system in studentsâ score data processing, by writing name and score of students on a paper that has been provided. The main drawback of this system is required many times and effort with the result that delayed the information of the data. The purpose of this research is to develop the application of data processing that is computerized. The application of studentsâ score data processing in this research is an application that handles studentsâ subject score data processing at SMAN 1 South Amanuban. This application is designed using Microsoft Visual Basic 6.0 and MySql.Hopefuly, the application of studentsâ score data processing base on computer can facilitate the teachers to manage the studentsâ score more quickly and effectively.Keyword: data processing, student, Visual Basic, MySql.